Effectiveness of PBL STEM to Improve Problem Solving Skills - Wachidah Hayuana; Hadi Suwono; Frida Kunti Setiowati (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2023)
STEM PBL emphasizes integrating several aspects of science, such as technology and design, where in this aspect, there will be an innovative engineering process based on science and mathematics that aims to carry out innovation and problem-solving. The research design is a non-equivalent pre-test and post-test control group design—the tests conducted by pre-test and post-test of the learning process in experiment and control groups. The experiment and the control group were conducted in two classes with different treatments; the experiment class used the PBL STEM model, while the control class was treated using a conventional model. The results present that the average percentage of the student’s problem-solving in the experiments class increased after implementing the STEM PBL model. More students were experts in all aspects of problem-solving in the post-test compared with the pre-test.